al-Taḥlīl ʿan Taʿlīm Mahārah al-Qirāʾah al-Qāʾim ʿalā Ṭarīqah al-Qawāʿid wa al-Tarjamah wa Ḥifẓ Qawāʿid al-Ṣarf li-Ṭullāb al-Ṣaff al-Ḥādī ʿAshar fī Madrasah Miftāḥ al-Salām al-ʿĀliyah al-Ahliyah Mīdān: Analysis of Maharah Qira'ah Learning Through the Qawa’id Tarjamah Method and Memorization of Shorof Rules in Grade XI Students at MAS Miftahussalam Medan - Andini Rahmawati; Fahrurrozi S (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
Reading skill (mahārah qirā’ah) is one of the essential competencies in Arabic language learning, particularly in Madrasah Aliyah. However, many students still face difficulties in understanding Arabic texts due to limited vocabulary, weak mastery of grammar, and insufficient understanding of ṣarf rules. This study aims to analysis the implementation of mahārah qirā’ah learning through the qawāʿid tarjamah method combined with memorization of ṣarf rules among eleventh-grade students at MAS Miftahussalam Medan, as well as to examine students’ responses and motivation toward its application. This research employed a qualitative descriptive method with Arabic language teachers and eleventh-grade students as research subjects. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. Data validation was carried out through triangulation, prolonged engagement, and member checking. The findings are expected to provide theoretical contributions to the development of Arabic teaching strategies, particularly in enhancing mahārah qirā’ah. Practically, this study offers benefits for teachers in selecting effective teaching methods, for students in improving their comprehension of Arabic texts, and for schools in designing more contextual learning strategies. Keywords: Arabic Learning, Mahārah Qirā’ah, Qawāʿid Tarjamah, Ṣarf Rules. ملخص إن مهارة القراءة تعد كفاءة أساسية في تعلم اللغة العربية، وخاصة في المرحلة الثانوية (المدرسة العليا الإسلامية). ومع ذلك، لا يزال كثير من الطلاب يواجهون صعوبات في فهم النصوص العربية بسبب محدودية المفردات وضعف إتقان القواعد النحوية وقلة الفهم لقواعد الصرف. وتهدف هذه الدراسة إلى تحليل تنفيذ تعليم مهارة القراءة من خلال طريقة القواعد والترجمة المقرونة بحفظ قواعد الصرف لدى طلاب الصف الحادي عشر في مدرسة مفتاح السلام الإسلامية بمدينة ميدان، وكذلك لمعرفة استجابة الطلاب ودافعيتهم تجاه تطبيقها. والمنهج المستخدم في هذه الدراسة هو المنهج الوصفي النوعي مع معلمي اللغة العربية وطلاب الصف الحادي عشر بوصفهم عينة البحث. وقد جُمعت البيانات من خلال الملاحظة والمقابلة والوثائق، ثم حُلّلت باستخدام نموذج تقليل البيانات وعرضها واستخلاص النتائج. وتم التحقق من صحة البيانات بالتثليث وزيادة المثابرة وعرض النتائج على المشاركين. ومن المتوقع أن تسهم نتائج هذه الدراسة في إثراء الجانب النظري لتطوير استراتيجيات تعليم اللغة العربية، وخاصة في مجال إتقان مهارة القراءة. أما من الناحية العملية، فإن هذه الدراسة تقدم فائدة للمعلمين في اختيار طريقة تدريس فعّالة، وللطلاب في تحسين فهم النصوص العربية، وللمدرسة في وضع استراتيجية تعليمية أكثر ارتباطا بسياق التعلم. الكلمات المفتاحية: تعليم اللغة العربية، مهارة القراءة، القواعد والترجمة، قواعد الصرف.